A new principle applied to the determination of calcium in biological materials by flame photometry - Fawcett, J. K. (1961)
The effect of magnesium sulphate in releasing calcium emission from interference by phosphate and sulphate has been investigated. Samples were diluted in 10 mM MgSO(4), 2 mM NaCl, giving final calcium concentrations of about 0·05 to 0·10 mM. In this diluent, galvanometer readings were proportional to calcium concentrations up to 0·4 mM. The magnesium sulphate released calcium emission from depression by phosphate and sulphate. The excess sodium chloride eliminated enhancement of calcium emission by added sodium and potassium in the sample. Subtraction of background readings excluded direct interference. A 3% correction was made for the effect of the viscosity of 1: 50 plasma dilutions. Satisfactory recoveries of added calcium were obtained from plasma, urine, and faeces using the diluent described above. Results on urine and faeces correlated closely with those obtained by an EDTA titration method. Results on plasma were consistently 2% higher by flame photometry than by EDTA titration. Other methods of calcium determination, depending on the use of radiation buffers or standard addition, were found to be unsatisfactory because of variable interference by phosphate at different calcium levels.